ANALYSIS OF RED BLOOD CELL DISTRIBUTION WIDTH COEFFICIENT OF VARIATION ON STROKE PATIENT - Kartika Paramita; Agus Alim Abdullah; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Stroke is a functional disorder attributed to acute focal or global brain injury by vascular cause and persists more than 24 hours. Stroke is divided into ischemic and hemorrhagic strokes. Red Blood Cell Distribution Width (RDW) is a measurement of erythrocyte volume variation in blood circulation. Increased RDW reflects the inflammation that plays a role in the development of atherosclerosis in stroke. This study aims to analyze differences in RDW-CV values in patients with stroke. The design was cross-sectional with a retrospective approach, secondary data from medical records of inpatients with stroke from January to December 2016 at the Dr. Wahidin Sudirohusodo Hospital. The study population consisted of 490 patients aged ≥ 18 years old. The Kruskal-Wallis, Mann-Whitney, and Anova one way tests were used to analyze differences in RDW-CV values in patients with ischemic and hemorrhagic stroke. Mann-Whitney test results showed no significant difference in RDW-CV values between groups of ischemic and hemorrhagic stroke (p 0.96). Kruskal-Wallis and Anova one way tests showed no significant difference in RDW-CV values between four groups of patient outcomes in ischemic and hemorrhagic stroke (p 0.13 and p 0.35 consecutively). There were no significant RDW-CV values between ischemic and hemorrhagic stroke. There was no significant difference between RDW-CV values of four groups of patient outcomes in ischemic and hemorrhagic stroke. RDW-CV values cannot be used to distinguish both ischemic and hemorrhagic stroke, including the prediction of stroke mortality